An advanced training environment for vessels' last mile navigation. (2015) - Longo, Francesco; Nicoletti, Letizia
This article presents the design, development and prototyping of an advanced training environment for vessels' operations in the last mile of navigation. The main idea is to recreate the typical conditions in which operators are usually involved, including manoeuvres of large ships within the harbour area, tugboat operations to support ship manoeuvres and traffic. The system architecture includes three interoperable simulators, and this article focuses on one of the simulators, the tugboat simulator, presenting the system general architecture, the software design and development phase and the hardware integration. In particular, the 3D geometric models and the virtual environments (based on the port of Livorno, Italy) are introduced and described, the tugboat motion equations at sea (based on a 6 Degree of Freedom model) and the equations ruling the ship-tugboat interactions are presented and discussed; finally, specific information about the hardware integration (recreation of a tugboat bridge replica) is given.